Demand Conditions and Related Industries on Export Performance in the Zimbabwean Manufacturing Sector - Sibanda, Brian (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2025)
The Zimbabwean manufacturing sector has, for the past two decades, been plagued by significant systemic challenges ranging from volatile economic conditions, poor sector-wide performance capacity utilisation and poor expert performance. Zimbabwe‘s manufacturing sector has continued to post poor performance returns as evidenced by the declining manufacturing and export returns. Performance has been weakened further by volatile economic conditions, access to forex challenges, weak supply chain linkages, and inadequate innovation ecosystems have hindered sustainable growth. The hypothesised contribution of demand conditions and related and supporting industries to export performance notwithstanding, there is limited continuous research on this subject more so, focusing on Zimbabwe given its unique economic climate. In this regard, this study sought to investigate the effect of demand conditions and related and supporting industries on export performance in the Zimbabwean manufacturing sector. The study employed a descriptive research design, using structured questionnaires to collect data from 384 officials from active manufacturing exporters. Multiple Linear Regression Analysis (MLR) was used to analyse the findings. The study found that both demand conditions and related and supporting industries have a significant positive effect on export performance. The study concludes that favourable demand conditions and robust related and supporting industries are critical for enhancing export performance in Zimbabwe‘s manufacturing sector. The study has contributed to theory, policy and practice by providing empirical evidence from Zimbabwe, proposing policy recommendations to policymakers in Zimbabwe and practical solutions to the manufacturing sector.